The Influence of Internship Experience, Motivation, and Academic Achievement on Students' Readiness in Entering the World of Work with Self Efficacy as a Moderating Variable (Study on Management Students at Muhammadiyah University of Sidoarjo): Pengaruh Internship Experience, Motivation, dan Academic Achievement Terhadap Kesiapan Mahasiswa dalam Memasuki Dunia Kerja dengan Self Efficacy sebagai Moderating Variable (Studi Pada Mahasiswa Manajemen Universitas Muhammadiyah Sidoarjo) - Lestari, Fitri Dwi; Ubaidillah, Hasan (Journal of Islamic and Muhammadiyah Studies, 2022)
This study aims to determine the effect of Internship Experience, Motivation, and Academic Achievement on students' readiness to enter the world of work and to find out that Self Efficacy moderates the effect of Internship Experience, Motivation, and Academic Achievement on students' readiness to enter the workforce. This is a descriptive study using quantitative methods. Sampling was carried out using the Probability Sampling technique using the Simple Random Sampling method and collecting data using a questionnaire. The population of 428 people using the Slovin formula was obtained as many as 81 respondents. Using multiple linear regression, MRA, and hypothesis testing in the SPSS version 22 program. The results of the study prove that Internship Experience, Motivation, Academic Achievement have a significant effect on students' readiness to enter the world of work. Also, Self Efficacy strengthens the influence of Internship Experience and Motivation on students' readiness to enter the world of work, and Self Efficacy weakens the influence of Academic Achievement on students' readiness to enter the world of work.